Influence of Procurement Specification Development on Performance of The Energy Sector in Kenya - Mwangi, Monicah Wanjiku; Moronge, Dr. Makori (International Journal of Supply Chain and Logistics, 2020)
Purpose: The purpose of the study was to assess the influence of procurement specifications development on performance of the energy sector in Kenya with an aim of making recommendations on proper use of procurement specification development practices among energy sector in Kenya. Methodology: This research study adopted a descriptive research design approach. The researcher preferred this method because it allows an in-depth study of the subject. The target population was procurement officers in the energy sector in Kenya. The study employed stratified random sampling technique in coming up with a sample size of 154 respondents from a total of 253 target population in the energy sector in Kenya. The study combined two methods in its data collection that is, questionnaires and key informant interviews. After data collection, quantitative data was coded using Statistical Package for Social Science (SPSS) version 20. Data was analyzed through descriptive statistical methods such as means, standard deviation, frequencies and percentage. Inferential analyses were used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable. Results and conclusion: The independent variables reported R value of 0.796 indicating that there was perfect relationship between dependent variable and independent variables. R-Square is a commonly used statistic to evaluate model fit. R2 is 1 minus the ratio of residual variability. The coefficient of determination also called the R2 was 0.634. R2 value of 0.634 means that 63.4% of the corresponding variation in performance of the energy sector in procurement specification development in the energy sector in Kenya can be explained or predicted by (planning and analysis, stakeholder involvement, vetting and approvals, revision and storage) which indicated that the model fitted the study data. The Findings of the Study Indicated That Planning and Analysis, Stakeholder Involvement, Vetting and Approvals and Revision and Storage Have A Positive Relationship with Performance of The Energy Sector. Unique contribution to theory, policy and practice: The study recommended that companies in the energy sector should embrace drivers of procurement specification development and further researches should to be carried out in other institutions to find out if the same results can be obtained.